2017
DOI: 10.1097/mao.0000000000001395
|View full text |Cite
|
Sign up to set email alerts
|

Transcanal Endoscopic Ear Surgery for Middle Ear Cholesteatoma

Abstract: Transcanal endoscopic ear surgery was found to be an acceptable and safe technique for the exposure and eradication of middle ear and/or attic cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Not surprisingly, areas of limited visualization, such as the sinus tympani and epitympanum, have higher rates of recurrence (≥20%) . Application of the endoscope to the otologic armamentarium has implications for cholesteatoma surgery, as it allows the surgeon to visualize difficult‐to‐access regions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, areas of limited visualization, such as the sinus tympani and epitympanum, have higher rates of recurrence (≥20%) . Application of the endoscope to the otologic armamentarium has implications for cholesteatoma surgery, as it allows the surgeon to visualize difficult‐to‐access regions …”
Section: Introductionmentioning
confidence: 99%
“…5 Application of the endoscope to the otologic armamentarium has implications for cholesteatoma surgery, as it allows the surgeon to visualize difficult-to-access regions. 2,6 Recurrent cholesteatoma requires revision surgery, which contributes significantly to the cost of care. In fact, operating room costs remain among the largest contributors to healthcare expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…Following a literature search, there was no clear patient selection criteria proposed. Both Tarabichi et al [15] and Glikson et al [16] recommended endoscopic surgery when the cholesteatoma did not extend posterior to the anterior limb of the lateral semi-circular canal. These are the same criteria we use in both our centres.…”
Section: Discussionmentioning
confidence: 99%
“…Transcanal EES has been found to be an acceptable and safe technique for the exposure and eradication of middle ear and/or attic cholesteatoma. 12,13 A study by Mürbe revealed that two-handed endoscopic manipulation yields significantly smaller tremor amplitudes than one-handed manipulation; though, in clinical otological surgery, operators basically manipulate the endoscope with one hand and surgical instruments with the other. 9 Neudert analyzed the hand tremor of students during 28 days of surgical training of tympanic membrane reconstruction using both hands but did not find any significant reduction of hand tremor.…”
Section: Discussionmentioning
confidence: 99%